The effects of vestibular rehabilitation on dizziness and balance problems in patients after traumatic brain injury: a randomized controlled trial. (January 2019) - Kleffelgaard, Ingerid; Soberg, Helene Lundgaard; Tamber, Anne-Lise; Bruusgaard, Kari Anette; Pripp, Are Hugo; Sandhaug, Maria; Langhammer, Birgitta
Objective: To investigate the effects of group-based vestibular rehabilitation in patients with traumatic brain injury. Design: A single-blind randomized controlled trial. Setting: University Hospital (recruitment and baseline assessments) and Metropolitan University (experimental intervention). Subjects: A total of 65 patients (45 women) with mild-to-moderate traumatic brain injury (mean age 39.4 ± 13.0 years) were randomly assigned to intervention ( n = 33) or control group ( n = 32). Intervention: Group-based vestibular rehabilitation for eight weeks. Participants were tested at baseline (3.5 ± 2.1 months after injury) and at two post-intervention follow-ups (2.7 ± 0.8 and 4.4 ± 1.0 months after baseline testing). Main measures: Primary outcome: Dizziness Handicap Inventory. Secondary outcome: High-Level Mobility Assessment Tool. Other outcomes: Vertigo Symptom Scale; Rivermead Post-concussion Symptoms Questionnaire; Hospital Anxiety and Depression Scale; and Balance Error Scoring System. Between-group differences were analyzed with a linear mixed-model analysis for repeated measurements. Results: At baseline, no group differences were revealed (personal factors, clinical characteristics and outcome measures). At the first follow-up, statistically significant mean differences in favor of the intervention were found in the primary (−8.7, 95% confidence interval (CI): −16.6 to −0.9) and secondary outcomes (3.7 points, 95% CI: 1.4–6.0). At the second follow-up, no significant between-group differences were found. No significant between-group differences in the other outcomes were found at the two follow-ups. Conclusion: The intervention appeared to speed up recovery for patients with dizziness and balance problems after traumatic brain injury. However, the benefits had dissipated two months after the end of the intervention.